Fundamentos de la ética (2013)
ABSTRACT: This text presents a modest analysis of the status of ethics in Kant and the function of duty and moral law in human life, having as reference only the Groundwork of the Metaphysic of Morals. This analysis aims to show the yields of a reading con-cerning the problem stated. A tension between the Kantian duty and the Freudian law is a plus. The latter, indeed, is transmitted one by one under the form of castration and is assimilated despite the subject.